2017
DOI: 10.1108/ccsm-03-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing knowledge sharing in high-tech firms

Abstract: Purpose The purpose of this paper is to explore the development of knowledge sharing from the perspectives of broaden-and-build theory and expectancy theory. Its research purpose is to understand how knowledge sharing is driven by such predictors as optimism, pessimism, and positive affect through their complex interactions with collectivism or power distance. In the proposed model of this study, knowledge sharing relates to optimism and pessimism via the partial mediation of positive affect. At the same time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 135 publications
1
18
0
Order By: Relevance
“…In the present study, horizontal individualism and vertical collectivism moderate the relationship between self-efficacy and intention to mentor. This result in in line with recent research which has also found collectivism (Chiu et al , 2018) or individualism (Mukherjee et al , 2012; Alcántara-Pilar and Del Barrio-García, 2015) play a moderator role in different study contexts. The nature of the moderating effect shows that the positive relationship between self-efficacy and intention to mentor becomes stronger when the respondents are inclined toward vertical collectivistic or horizontal individualistic values.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, horizontal individualism and vertical collectivism moderate the relationship between self-efficacy and intention to mentor. This result in in line with recent research which has also found collectivism (Chiu et al , 2018) or individualism (Mukherjee et al , 2012; Alcántara-Pilar and Del Barrio-García, 2015) play a moderator role in different study contexts. The nature of the moderating effect shows that the positive relationship between self-efficacy and intention to mentor becomes stronger when the respondents are inclined toward vertical collectivistic or horizontal individualistic values.…”
Section: Discussionsupporting
confidence: 92%
“…Individuals from collectivistic culture are more willing to help others (Moorman and Blakely, 1995), the expatriates tend to receive more mentoring in countries which are associated with collectivistic cultural values than in countries with individualistic values (Feldman and Bolino, 1999), and mentees with collectivistic values receive significantly more mentoring than individuals with individualistic orientation (Richard et al , 2009). Recent research has also found collectivism as a significant moderator which enhances information sharing in organizations (Chiu et al , 2018). These findings about the impact of cultural values on the mentoring process show the potential role of these cultural values in an individual’s intention to mentor others.…”
Section: Individualism-collectivismmentioning
confidence: 99%
“…In an environment where a certain quality of work must be maintained (i.e. the collective goal), employees in a firm must collaborate effectively (Chiu et al , 2018). A common goal (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…One or more agents receive and use the "tacit or/ and explicit knowledge" provided by another agent intentionally to capture the experiences and skills between them (Lin et al, 2020;Ma et al, 2014). Today, the success of organisations is evaluated by the ability of their leaders to motivate their subordinates and teams to exchange and share ideas, experiences, insights and skills (Chiu et al, 2018). KS process is a strategic priority and crucial capability that organisations use as an effective means to improve and develop knowledge and stimulate a rapid response to change and innovation and build competitive advantages (Nugroho, 2018;Wu and Lin, 2013).…”
Section: Theoretical Background and Hypothesis Formulation 21 Knowledge Management Processesmentioning
confidence: 99%